2023
DOI: 10.1111/bjh.18763
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transplant lymphoproliferative disorder: Update on treatment and novel therapies

Abstract: Post-transplant lymphoproliferative disorder (PTLD) is rare and heterogeneous lymphoid proliferations that occur as a result of immunosuppression following solid organ transplant (SOT) and haematopoietic stem cell transplant (HSCT) with the majority being driven by EBV. Although some histologies are similar to lymphoid neoplasms seen in immunocompetent patients, treatment of PTLD may be different due to difference in pathobiology and higher risk of treatment complications. The most common treatment approach in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…Recent study ( 59 ) identified in EBV-positive DLBCL relatively frequent mutations of SOCS1 , NOTCH2 , and NOTCH1 genes, suggesting that these mutated genes may have a pathogenic role in this type of lymphoid malignancy. While current therapies for in transplant patients affected by the EBV-driven lymphoproliferative disorders typically include tempering immunosuppressive regimens, often combined with CD20-targeting immunotherapy, or multiagent immunochemotherapy ( 60 ), the conceptually most advanced clinical trials focus on immunotherapy with EBV-detecting cytotoxic T cells ( 61 ) LMP-targeting CAR T cells ( 62 ), or anti-EBV vaccines ( 62 ).…”
Section: Epstein-barr Virus As Substitute Of Bcr Signalingmentioning
confidence: 99%
“…Recent study ( 59 ) identified in EBV-positive DLBCL relatively frequent mutations of SOCS1 , NOTCH2 , and NOTCH1 genes, suggesting that these mutated genes may have a pathogenic role in this type of lymphoid malignancy. While current therapies for in transplant patients affected by the EBV-driven lymphoproliferative disorders typically include tempering immunosuppressive regimens, often combined with CD20-targeting immunotherapy, or multiagent immunochemotherapy ( 60 ), the conceptually most advanced clinical trials focus on immunotherapy with EBV-detecting cytotoxic T cells ( 61 ) LMP-targeting CAR T cells ( 62 ), or anti-EBV vaccines ( 62 ).…”
Section: Epstein-barr Virus As Substitute Of Bcr Signalingmentioning
confidence: 99%
“…The risk of lymphoproliferative disease is 12-fold higher in KTR compared with a matched non-transplant population [ 73 ]. PTLD is associated with EBV in >80% cases in Europe and United States [ 74 , 75 ]. The negative EBV serostatus of the recipient is the greatest risk factor of EBV-induced PTLD, since 90% of early onset PTLD occurred in seronegative recipients and mostly in the first year post-transplantation [ 76 ].…”
Section: Epstein–barr Virusmentioning
confidence: 99%
“…Another approach involving prophylactic infusion of donor EBV‐specific CTL in high‐risk HSCT patients has been shown to be feasible and safe and is likely to be effective 61 . For further information, a recent update on novel therapies in PTLD is recommended 62 …”
Section: Ebv‐associated Ptldsmentioning
confidence: 99%